Influenza A (H1N1) 2009 reinfection in Thailand - Satariya Trakulsrichai (2018)
In 2009, a novel influenza A (H1N1) virus emerged and rapidly spread around the world, leading to a pandemic. In contrast to the high rate of primary infection, reinfection with influenza A (H1N1) 2009 is rather rare. In this report, we describe a case of influenza A (H1N1) 2009 reinfection that occurred within an interval of 5. months in Thailand. © 2012 King Saud Bin Abdulaziz University for Health Sciences.